HUBUNGAN TINGKAT KEPERCAYAAN DIRI DENGAN JERAWAT (ACNE VULGARIS) PADA REMAJA KELAS X-XII IPA SMAN 9 BINSUS MANADO - Tampi, Feggy Esterlita Irene; David, Lydia; Opod, H. (Universitas Sam Ratulangi, 2016)
Abstract: Acne is a chronic inflammatory disease of the pilosebaceous follicles which generally occurs in adolescence and can heal itself. Teenagers who have acne problems often have problems associated with self-confidence. Self-confidence is an attitude or feeling confident of his own abilities. Individuals who have the self-confidence have a positive feelings toward him. Individuals who do not believe themselves to have shy behavior and cannot adjust to the environment. This study aims to assess the scientific self-confidence level correlation with acne in adolescents classes X-XII Science at SMAN 9 Binsus Manado. This research uses a cross-sectional study with a sample of 130 people. The results showed the value of correlation coefficient are -0.144 where this value showed a negative correlation between self-confidence with acne and the value of correlation coefficient are 0.144, the correlation between two variables is very weak with significance value at 0.103 > 0.05, which means there is no significant correlation between self-confidence with acne. So it can be concluded that this hypothesis is rejected, meaning that there is no significant correlation between self-confidence with acne.Keywords: Acne, Self-confidence, AdolescentsAbstrak: Jerawat adalah penyakit peradangan menahun folikel pilosebasea yang umumnya terjadi pada masa remaja dan dapat sembuh sendiri. Remaja yang mengalami masalah jerawat seringkali mempunyai masalah yang berkaitan dengan kepercayaan diri. Kepercayaan diri merupakan suatu sikap atau perasaan yakin atas kemampuan sendiri. Individu yang mempunyai kepercayaan diri memiliki perasaan positif terhadap dirinya. Individu yang tidak percaya diri mempunyai perilaku malu dan tidak bisa menyesuaikan diri dengan lingkungan. Penelitian ini bertujuan untuk mengkaji secara ilmiah hubungan tingkat kepercayaan diri dengan jerawat pada remaja kelas X-XII IPA SMAN 9 Binsus Manado. Penelitian ini menggunakan jenis penelitian rancangan cross sectional dengan jumlah sampel 130 orang. Hasil penelitian menunjukkan nilai koefisien korelasi sebesar -0,144 dimana nilai ini menujukkan hubungan negatif antara kepercayaan diri dengan jerawat dan dari nilai koefisien korelasi 0,144 maka hubungan antara kedua variabel sangat lemah dengan nilai signifikansi 0,103 > 0,05 yang berarti tidak terdapat hubungan signifikan antara kepercayaan diri dengan jerawat. Jadi dapat disimpulkan bahwa hipotesis dalam penelitian ini ditolak, artinya tidak terdapat hubungan signifikan antara kepercayaan diri dengan jerawat.Kata Kunci: Jerawat, Kepercayaan diri, Remaja